Interpretetive dictionary: competence, qualification, education, knowledge - Brockmann, Michaela [Verfasser]; Clarke, Linda [Verfasser]; Winch, Christopher [Verfasser]; Hanf, Georg [Verfasser]; Méhaut, Philippe [Verfasser]; Westerhuis, Anneke [Verfasser] (My University, 2011)
This chapter "consists of an analytical and interpretetive dictionary of central concepts in European VET, drawn from the four countries in this study. [...] The intention in this chapter is to contrast the varying conceptions of different key terms in EU discourse, in official national discourses and in everyday usage in and around the workplace in the different countries." The chapter is structured around a set of the five following categorial concpets: education, qualification, knowledge, competence and skill. For each of these concepts, an interpretetive commentary on different ambiguities that may arise in the translation of terms and on differences and similarities within und between concepts, is given. (Hrsg., BIBB-Doku)
Keywords: Bildung; Berufsbildung; Weiterbildung; Qualifikation; Wissen; Kompetenz; Definition; Bundesrepublik Deutschland; England; Frankreich; Niederlande